2018
DOI: 10.1080/08870446.2018.1456659
|View full text |Cite
|
Sign up to set email alerts
|

Adult self-image and well-being after testicular cancer: The role of agency and meaning

Abstract: Assessment of adult self-image might be useful in identifying risk for poor adjustment. Interventions that target agency and meaning might facilitate developmental goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Negative body image, 33 , 42 , 43 anxiety, depression, 44 , 45 and fatigue 46 , 47 decreased patient well-being. Moreover, treatment side effects, especially pain, 48 correlated with lower well-being.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative body image, 33 , 42 , 43 anxiety, depression, 44 , 45 and fatigue 46 , 47 decreased patient well-being. Moreover, treatment side effects, especially pain, 48 correlated with lower well-being.…”
Section: Resultsmentioning
confidence: 99%
“…95 One study suggested that patients may find meaning in cancer by: attempting to define the disease, viewing cancer as a ‘‘divine test’’, or as a catalyst for positive self-reconstruction. 96 Intrinsic factors, such as self-esteem, 44 religious faith, 97 spiritual well-being, 98 and positive coping strategies, 99 correlated with meaning discovery. Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs.…”
Section: Resultsmentioning
confidence: 99%
“…These include accomplishing relationship and career goals, 13,15,21 accepting the possibility of an uncertain future, 22 and solidifying beliefs about the self as an independent adult agent. 34 EA cancer survivors who have fewer tangible resources, less flexibility to accept goal change, and stronger visions of the self as an independent adult agent may be at greater risk to experience psychological distress as a result of cancer-related financial stress.…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of new diagnoses of testicular cancer occur in young adults (ages 18-29) (NCI, 2019), a life stage marked by establishing independence and by challenges in relationships and career pursuits (Arnett, 2000). Young men report disruptions in body image, elevated anxiety, changes in sexual confidence, and lowered adult self-image after treatment (Ryan & Hoyt, 2018;Smith et al, 2016). Such adverse outcomes can be perceived as inconsistent with masculine identity, contributing to psychological distress and declines in physical health (Hoyt, Stanton, Irwin, & Thomas, 2013).…”
mentioning
confidence: 99%